(untitled) (Journal of Dhaka Medical College, 2011)
Most of the hospitalized patients are anaemic to some degree in our country and sometimes need blood transfusion. Complications of blood transfusion are rare but can be life-threatening. Since 2005, it has been a legal requirement that all serious adverse reactions attributable to the safety or quality of blood transfusion are reported. Most reported complications are because of transfusion of mismatched blood products and are avoidable with proper vigilance. A 45 year old female who underwent salpingo-oophorectomy with total abdominal hysterectomy for torsion of ovarian cyst and was transfused one unit of blood peroperatively. Blood grouping was accidentally incorrect and cross matching was not done. This mismatched blood transfusion resulted in acute renal failure. Patient was referred from the private hospital to Dhaka Medical College Hospital, Dhaka and was managed by forced alkaline diuresis and later, haemodialysis. Key words: Mismatched blood transfusion; haemolytic transfusion reaction DOI: 10.3329/jdmc.v19i2.7089 J Dhaka Med Coll. 2010; 19(2) : 154-157